IT-Based Learning System for TKJ Subjects in Vocational Schools - Cahyaning, Cindy; Azizah, Nur; Rohmatulloh, Muhammad Aziz; Reynendra, Julian Rafly; Pratama, M. Fikri; Nuruddin, Farhan (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to determine the application of IT-based learning at SMK Muhammadiyah 1 Taman in improving the quality of learning in the field of Computer and Network Engineering (TKJ). This research uses descriptive qualitative methods with data obtained through observation, interviews and document study. The results of the research show that Muhammadiyah 1 Taman Vocational School implements IT-based learning with various strategies, namely: Implementation of the Independent Curriculum which gives students freedom in choosing learning materials. TKJ, Utilization of digital learning media such as video, animation, and simulation, Use of online platforms to provide learning materials, assignments, and assessment of student learning outcomes, Application of group learning, Development of educator competency through training and workshops, Implementation of these strategies shows SMK's commitment Muhammadiyah 1 Taman in improving the quality of learning in the TKJ field in the digital era. The efforts made by SMK Muhammadiyah 1 Taman should be appreciated and can be an inspiration for other schools in improving the quality of learning in the TKJ field in the digital era.